2019
DOI: 10.1021/acs.est.8b06410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone on the Photochemical and Photophysical Properties of Dissolved Organic Matter

Abstract: This study focused on the effects of ozonation on the photochemical and photophysical properties of dissolved organic matter (DOM). Upon ozonation, a decrease in DOM absorbance was observed in parallel with an increase in singlet oxygen (1O2) and fluorescence quantum yields (Φ1O2 and ΦF). The increase in Φ1O2 was attributed to the formation of quinone-like moieties during ozonation of the phenolic moieties of DOM, while the increase in ΦF can be explained by a significant decrease in the internal conversion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 63 publications
10
78
0
1
Order By: Relevance
“…The 1O2 -values for the selected low molecule DOM analogs were calculated and the results showed that the 1O2 for BP ((8.48 ± 0.09) × 10 −2 ) containing a ketone functionality and for p -BQ ((2.92 ± 0.01) × 10 −2 ) with a quinone functional group were much higher than the value of 1O2 for the other analogs, which is in accordance with the results observed in previous literature ( Leresche et al, 2019 ;McNeill and Canonica, 2016 ). Thus, the formation of quinone and ketone functional groups during the UV/chlorine treatment are the reason for the increase of the 1O2 from SRFA and SRNOM.…”
Section: Effect Of Uv/chlorine Treatment On 1 O 2 and •Oh Generation From Srfa And Srnomsupporting
confidence: 89%
“…The 1O2 -values for the selected low molecule DOM analogs were calculated and the results showed that the 1O2 for BP ((8.48 ± 0.09) × 10 −2 ) containing a ketone functionality and for p -BQ ((2.92 ± 0.01) × 10 −2 ) with a quinone functional group were much higher than the value of 1O2 for the other analogs, which is in accordance with the results observed in previous literature ( Leresche et al, 2019 ;McNeill and Canonica, 2016 ). Thus, the formation of quinone and ketone functional groups during the UV/chlorine treatment are the reason for the increase of the 1O2 from SRFA and SRNOM.…”
Section: Effect Of Uv/chlorine Treatment On 1 O 2 and •Oh Generation From Srfa And Srnomsupporting
confidence: 89%
“…Similar decreases in molecular weight due to ozonation are observed using direct measurements such as SEC 1,13,15 and sequential ultrafiltration, 14 as well as using UV-vis spectroscopy-derived parameters. 21,33,34,58 Large decreases in SUVA254 are observed with increasing specific O3 doses (Figures 1c and S4c), which agrees with previous observations 12,13,[16][17][18]34 and correlates with decreasing aromaticity.…”
Section: Introductionsupporting
confidence: 92%
“…Many of the oxidized product formulas observed here occupy the same van Krevelen space as formulas associated with triplet DOM and singlet oxygen production, 53,55 confirming observations that ozonation increases quantum yields of these species in undiluted wastewater. 20,21 Finally, the molecular composition of DOM observed after ozonation is highly oxidized, with many formulas with O:C values that are outside the range encountered in natural and engineered waters (i.e., >1.0). 17,41,42,53,55,65…”
Section: Dom Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…天然有机质(NOM)一般由中等分子量的疏水性芳香聚电解质组成,包括多 糖、多肽、氨基酸、蛋白质和腐殖质等 [76,77] ,且 NOM 对水环境中有机物光降解 的影响既有促进作用也有抑制作用 [78~80] . NOM 作为光敏化剂促进水中有机污染 物 光降解的机制主要是由于其吸收光能后发生电子跃迁形成激发单线态 NOM( 1 DOM*) [81,82] ,并发生系间窜跃形成激发三线态 NOM( 3 NOM*). 3 NOM*是…”
Section: 间接光老化unclassified